2022
DOI: 10.3390/ijms23158182
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Toxicity Induced by Chemical Agents

Abstract: Vision is an important sense for humans, and visual impairment/blindness has a huge impact in daily life. The retina is a nervous tissue that is essential for visual processing since it possesses light sensors (photoreceptors) and performs a pre-processing of visual information. Thus, retinal cell dysfunction or degeneration affects visual ability and several general aspects of the day-to-day of a person’s lives. The retina has a blood–retinal barrier, which protects the tissue from a wide range of molecules o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 157 publications
1
8
0
Order By: Relevance
“…The evidence supports the hypothesis that these compounds ( 3a – l ) slow the development of embryonic zebrafish into juveniles. However, every embryo that survived was later hatched and reached around 100 % of the treated and the negative control, consistent with the present findings [38] . The isolated compound ( 1a ) and the synthesis of benzimidazole derivatives ( 3a – l ) did not significantly alter the morphology of zebrafish embryos, according to the morphological studies of the embryos [39] Figure 5.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The evidence supports the hypothesis that these compounds ( 3a – l ) slow the development of embryonic zebrafish into juveniles. However, every embryo that survived was later hatched and reached around 100 % of the treated and the negative control, consistent with the present findings [38] . The isolated compound ( 1a ) and the synthesis of benzimidazole derivatives ( 3a – l ) did not significantly alter the morphology of zebrafish embryos, according to the morphological studies of the embryos [39] Figure 5.…”
Section: Resultssupporting
confidence: 88%
“…However, every embryo that survived was later hatched and reached around 100 % of the treated and the negative control, consistent with the present findings. [38] The isolated compound (1a) and the Figure 3. Survival rates of zebrafish embryos treated with citral (1a) and benzimidazole derivatives (3a-l) at 0-96 hpf.…”
Section: S No Compoundsmentioning
confidence: 99%
“…The recent methanol poisoning outbreak during the Covid-19 pandemic was the most signi cant methanol poisoning in Iran and the world. Visual symptoms due to methanol poisoning might appear hours after ingestion, ranging from a progressive decrease in vision to dyschromatopsia, scotoma, and photophobia (15). This study found signi cant changes in inner retinal layers and super cial vasculature.…”
Section: Discussionmentioning
confidence: 51%
“…The recent methanol poisoning outbreak during the Covid-19 pandemic was the most significant methanol poisoning in Iran and the world. Visual symptoms due to methanol poisoning might appear hours after ingestion, ranging from a progressive decrease in vision to dyschromatopsia, scotoma, and photophobia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%